Tribunkaltim.co News Analysis on the Halt of Ladyboy Event in Samarinda - Jeri Rahmadani; Nurliah Nurliah (Yayasan Adra Karima Hubbi, 2023)
Background. This research aims to analyze and conclude information about Theo Van Leeuwen's exclusion and inclusion strategies in the East Kalimantan Tribune news when stopping the ladyboy event in Samarinda City. Purpose. Lesbian, gay, bisexual and transgender (LGBT) people in Indonesia are vulnerable to discrimination such as inequality in education, employment, health, social assistance, and freedom of expression or public space in society. Tribun Kaltim is a mass media that reported the termination of the ladyboy event in Samarinda. Method. This research method uses critical discourse analysis modeled by Theo Van Leeuwen to find out how one party or group is featured or omitted in the text. The research found 5 exclusion data and 32 inclusion data. Results. The results are in accordance with Theo Van Leeuwen's theory that a certain group or social actor can be eliminated and even marginalized in the text or discourse. The results also reinforce the concept of the hierarchy of media content influence in mass communication studies, which understands how news texts by certain media agencies can be influenced by internal and external factors, such as the background of journalists, media reader segmentation, media organization policies, and external news sources from media organizations. Conclusion. From the research results, it can be concluded that there are 5 exclusion data and 32 inclusion data.